Aplikasi game pada materi sumpah pemuda tingkat sekolah menengah pertama - Gibran, Agil Matien (Indonesian Institute for Counseling, Education and Therapy (IICET), 2024)
History, studying it is one of the obligations that students need to do, at least they know about national history. The learning process tends to be boring, making students less interested in learning more history, or more active in the learning process. Games become one of the solutions to be a learning media that can increase learning interest and make students more active in finding information about the studies. The purpose of this research is to try to make Game-Based Learning using the Multimedia Development Life Cycle (MDLC) method, where in MDLC there are stages that begin with the concept, design, material collection, assembly, testing, and finally distribution. The results of this study are expected to make this game as one of the learning media and attract students to be more motivated and also more active in the learning process.